Serologic survey of the wild boar (Sus scrofa) for Borrelia burgdorferi sensu lato - Juricová, Z; Hubálek, Z (Vector borne and zoonotic diseases (Larchmont, N.Y.), 2009)
Sera of 642 wild boars (Sus scrofa) shot by hunters in ten administrative regions of the Czech Republic during 1995-2000, were tested by indirect hemagglutination assay (IHA) for the presence of anti-Borrelia IgG. Antibodies to Borrelia burgdorferi sensu lato (Bb) were detected in serum samples from all 10 regions, and overall seroprevalence rate was 12.8%. Titres of antibodies ranged from 1:80 to 1:640. Borrelia antibodies were most frequent in the animals from three administrative regions of the Czech Republic: Moravskoslezsky (25.0%), Pardubicky (25.0%) and Královehradecky (24.1%), followed by the regions Plzen sky (16.7%), Olomoucky (13.3%), Jihomoravsky (12.8%), Vysoc ina (11.1%), Jihoc esky (11.1%), Zlínsky (10.3%), and Liberecky (8.9%). Seasonal seroprevalence rate increased in March and April, the peak was in May. The results suggest frequent exposure of wild boars to ixodid ticks infected with Bb, predominantly in rural and forested regions. The study also reviews the importance of wild boar in Lyme borreliosis (LB) ecology. Wild boar serology may provide another means of surveillance of endemic areas of LB.
Keywords: Česká republika; protilátky bakteriální; Antibodies, Bacterial; Czech Republic; Borrelia burgdorferi komplex; lymeská nemoc; Sus scrofa; Animals; Seroepidemiologic Studies; séroepidemiologické studie; roční období; Seasons; Borrelia burgdorferi Group; zvířata; Lyme Disease